Makna Simbolik Zikir Pada Jemaah Tarekat Qadiriyah Naqsabandiyah (Studi Kasus Pada Jemaah Tarekat Naqsabandiyah di Pondok Pesantren Sirnarasa Ciamis) - Izzah Faizah Siti Rusydati Khaerani; Yuyun Nurlaen (Jurnal Studi Agama dan Masyarakat, 2019)
This paper discusses symbolic meaning of the ritual of zikir in the Qadiriyah Naqsabandiyah followers (TQN) in Sirnarasa Ciamis “. This research uses a case study method assisted with a symbolic interactional approach. The focus of his study is the followers of the Qadiriyah Naqsabandiyah (TQN) who have been practicing zikir for more than 3 years. The results of the study found the symbolic meaning of zikir as follows (1) There is no space for immersion in worldly affairs because the essence of each work is part of zikir to Allah 2). Zikir is a blessing of God, for ordinary people enjoying zikir is sought, in order to feel the temporary in his life. 3). This pleasure creates a peace of mind, because people who always do zikir are believed to be always remembered by God, forgiven of sin, always have hope that every prayer is accpeted, the most important part of zikr is to feel knowing Allah. This is reflected by always loving kindness (jȃr al-khair), softening hearts, and miftah al ghaib (be opened things that we do not know yet).